Full information concerning vitiligo that causes cosmetological problems - Marasulova Madinabonu daughter of Arabboy; Mamatqulova Umida daughter of Mamaruzi; G'ofurjonova Irodaxon daughter of Qobiljon (Zien Journals, 2022)
This article illustrates more information about vitiligo which is widely known as white spot. Therefore, it also provides some causes of this disease likewise its prevalence, development and treatment.
Keywords: Hypomelanosis; Melanin; Allergic; Hyperpigmentation